Youth environmental volunteerism in Malaysia - Abdul Rahman, Haliza (Human Resource Management Academic Research Society, 2023)
Currently, youth have a stronger awareness of the issues and a greater stake in long-term sustainability, thus the environment is one area in which they ought to take the lead. Volunteerism as a form of civic participation, can be a powerful mechanism for giving youth a voice in decision making and promoting social inclusion in environmental governance in order to combat “the greying of the greens. Significantly, the participation of youth in environmental protection can be sought at levels and locations ranging from grass-roots activism and participation in conservation projects to policy-making bodies and NGOs. Thus, this article provides a conceptual overview of the youth volunteerism in environmental issues with analyzing and reviewing journal articles, reports, newspaper publications, and other relevant documents on youth environmental volunteerism. As conclusion, youth environmental volunteerism needs to be recognized, encouraged, supported and promoted at global, national and regional levels.